2016
DOI: 10.14260/jemds/2016/688
|View full text |Cite
|
Sign up to set email alerts
|

Vesicovaginal Fistula: Our Experience of 47 Cases in a Tertiary Care Hospital of West Bengal

Abstract: Vesicovaginal Fistula (VVF), an abnormal communication between the urinary bladder and vagina, is one of the most distressing and embarrassing health problem for the ladies. The present observational study was planned to inquire into the demographic and aetiologic pattern of vesicovaginal fistula and the long-term success rate of its surgical management following different techniques of repair in a tertiary care centre of West Bengal, India. MATERIAL AND METHODSA total of 47 patients with vesicovaginal fistula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…15 While another study conducted at tertiary case hospital of west Bengal Showed a bit lower success rate of 87.3%. 13 Another study conducted at Jimma university teaching hospital Ethiopia showed a success rate of 93.4% which is again comparable to my study. 14…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…15 While another study conducted at tertiary case hospital of west Bengal Showed a bit lower success rate of 87.3%. 13 Another study conducted at Jimma university teaching hospital Ethiopia showed a success rate of 93.4% which is again comparable to my study. 14…”
Section: Discussionsupporting
confidence: 86%
“…In this study 66.7% patients were having obstetric fistulas similar to some local and international studies 11,12 In another study conducted at a tertiary care hospital of west Bangal, 66% cases of VVF were tracked back to their obstetric causes and 34% patients could be linked up to gynaecological etiology like a complication of hysterectomy or after brachytherapy for carcinoma of cervix. 13 Among the 10 patients having obstetric fistulas, 7 were having home delivery and 3 were having delivery at some center by untrained personnel. This again is in sharp comparison to some of studies cited above.…”
Section: Discussionmentioning
confidence: 99%